PENERAPAN MODEL PEMBELAJARAN TERPADU TIPE NESTED DALAM PEMBELAJARAN PEMECAHAN MASALAH MATEMATIKA PADA MATERI INDUKSI MATEMATIKA - Aan Armini (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2020)
Through classroom action research, researchers seek to improve students 'mathematical problem solving abilities on mathematical induction material by using nested integrated learning methods and explore students' attitudes towards the application of the given learning model. The study was conducted during two cycles which included four stages of learning, namely: planning, implementation, observation, and reflection. The study was conducted in the odd semester of the 2019/2020 school year involving 34 students of class XI MIPA-2 SMAN 1 Garawangi, Kuningan. There are 2 types of research instruments used, namely tests and questionnaires. Based on the test results, it can be seen that in the post-test, the N-Gain index obtained was 0.61 (moderate). Meanwhile, based on the results of the questionnaire, it can be seen that 100% of students show a positive attitude. Thus, it can be concluded that the nested type integrated learning model can improve students' mathematical problem solving abilities on mathematical induction material and get a good appreciation with the presence of a positive attitude shown by all participants.